Robust counter electrodes from nanoporous NiM (M = Pt, Pd) alloys for dye-sensitized solar cells. (10th November 2015) - Yang, Peizhi; Tang, Qunwei
Graphical abstract: Highlights: NiPt and NiPd alloy CEs are synthesized with ZnO nanorod templates. The catalytic activity is markedly enhanced by alloying Ni with Pt or Pd. The stability of NiPt alloy CE is enhanced due to competitive dissolution reactions. The resultant liquid-junction DSSC with NiPt yields an optimal of 8.27%. Abstract: Alloys are a class of rising counter electrode (CE) electrocatalyst candidates for dye-sensitized solar cells (DSSCs). We present here the mild solution synthesis of NiM (M = Pt, Pd) alloys using zinc oxide nanorod templates and employment as CE electrocatalysts for liquid-junction DSSC applications. Due to the good matching of work functions to redox potential of I − /I3 − redox couples and reduced charge-transfer resistance at CE/electrolyte interface, the electrocatalytic activity of NiPt CE and therefore cell performances have been markedly enhanced, yielding a promising power conversion efficiency of 8.27% in the liquid-junction DSSC platform.